A likelihood framework for cryogenic scintillating calorimeters used in the CRESST dark matter search - Angloher, G; Banik, S; Benato, G; Bento, A; Bertolini, A; Breier, R; Bucci, C; Burkhart, J; Canonica, L; D’Addabbo, A; Lorenzo, SD; Einfalt, L; et al. (SpringerOpen, 2024)
Cryogenic scintillating calorimeters are ultra- sensitive particle detectors for rare event searches, particularly for the search for dark matter and the measurement of neutrino properties. These detectors are made from scintillating target crystals generating two signals for each particle interaction. The phonon (heat) signal precisely measures the deposited energy independent of the type of interacting particle. The scintillation light signal yields particle discrimination on an event-by-event basis. This paper presents a likelihood framework modeling backgrounds and a potential dark matter signal in the two-dimensional plane spanned by phonon and scintillation light energies. We apply the framework to data from CaWO4-based detectors operated in the CRESST dark matter search. For the first time, a single likelihood framework is used in CRESST to model the data and extract results on dark matter in one step by using a profile likelihood ratio test. Our framework simultaneously fits (neutron) calibration data and physics (background) data and allows combining data from multiple detectors. Although tailored to CaWO4-targets and the CRESST experiment, the framework can easily be expanded to other materials and experiments using scintillating cryogenic calorimeters for dark matter search and neutrino physics.